Emotion-focused care requested by hospital patients with dementia via advance care planning. (2nd February 2020) - Petty, Stephanie; Coleston, Donna Maria; Dening, Tom; Griffiths, Amanda
Abstract : Background: This study responds to international pressures to improve hospital care for patients with dementia. Aim: To reach a concise overview of ways to improve the emotional wellbeing of patients with dementia when in hospital by exploring their personal care requests. Methods: Written advance care planning (ACP) documents completed by patients with dementia and their caregivers were retrieved from a UK hospital ( n =21) and analysed using descriptive phenomenology. Findings: Care requests showed the changeable and personal nature of emotional distress and gave the responses that patients require from hospital staff. Responses included attending to physical health, offering reassurance, being with the patient, treating the patient as a person and providing a different physical environment. Conclusion: ACP documents offered a structured tool for informing care with succinct, personalised requests of patients with dementia. Patient requests were consistent with extensive literature defining person-centred care. Increased use of ACP in hospitals requires evaluation.